2017
DOI: 10.3168/jds.2017-12772
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Estimating lactation curves for highly inhomogeneous milk yield data of an F2 population (Charolais × German Holstein)

Abstract: Fitting of lactation curves is a common tool to obtain the entire milk yield as well as to estimate the main curve characteristic (such as day of peak milk yield) for a lactation. These models are primarily designed for dairy cattle, but have been applied to nondairy cattle breeds and also for other species. In this study we considered milk yield data of 197 F crossbred cows of Charolais and German Holstein (founder breeds) for the first and the beginning of the second lactation. The F cows showed a high varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…They found that the Wilmink, Wood, and the Ali and Schaeffer models were strongly affected by the size of the sample. Melzer et al [21] suggested that with more inhomogeneous data, using the Ali and Schaeffer model may be a good solution.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that the Wilmink, Wood, and the Ali and Schaeffer models were strongly affected by the size of the sample. Melzer et al [21] suggested that with more inhomogeneous data, using the Ali and Schaeffer model may be a good solution.…”
Section: Resultsmentioning
confidence: 99%
“…Karangelil et al [3], who analysed five different models used for describing the lactation curves of Chios sheep (Wood, Wilmink, Cobby and Le Du, Cappio Borlino, Djikstra), selected the Wood model as the best adjusted to daily AMS records. In 1987, Wilmink developed his function for adjusting test-day MY data [20] and since then, a number of researchers have used that model in their analysis [17,21,22]. For instance, Otwinowska-Mindur and Ptak [8], who obtained test-day MYs for Polish Holstein-Friesian cows used the Wilmink function to adjust lactation curves.…”
Section: Introductionmentioning
confidence: 99%
“…The results emphasize the necessity of pre-analyses of the significance of the feeding group effect. To investigate the goodness of fit for the different lactation models, it has to be considered that each model depends on the underlying data structure, such as duration of lactation and shape of lactation curve (Melzer et al, 2017). Lactation curves generally synthesize the main aspects of the shape of lactation and give good results when animal groups are homogeneous and fitted to average lactation patterns (Macciotta et al, 2015;Pulina et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…of feeding groups = additional feeding experiments within feeding group. trait MY, no model evaluation was conducted because the AS function is well established as shown in many former analyses (Buttchereit et al, 2010;Stamer et al, 2011;Melzer et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Multiple statistical models have been used to describe lactation curves. Quintero et al (2007), Cankaya et al (2011), Macciotta et al (2011), Graesbøll et al (2016), Hossein-Zadeh (2016) and Melzer et al (2017) reported on different lactation curve models, which are compared for dairy cattle. These papers show some models that can generally be expressed as Y ¼ g t; b ð Þ; where Y stands for milk yield at week or day t of lactation, and time t is on a time interval T. Here b is a vector which contains the unknown model parameters to be estimated from data.…”
Section: Introductionmentioning
confidence: 99%